Labor market effects of U.S. sick pay mandates - Stefan Pichler; Nicolas Ziebarth (W.E. Upjohn Institute for Employment Research, 2018)
This paper exploits temporal and spatial variation in the implementation of nine-city- and four state-level U.S. sick pay mandates to assess their labor market consequences. We use the synthetic control group method and traditional difference-in-differences models along with the Quarterly Census of Employment and Wages to estimate the causal effects of mandated sick pay on employment and wages. We do not find much evidence that employment or wages were significantly affected by the mandates that typically allow employees to earn one hour of paid sick leave per work week, up to seven days per year. Employment decreases of 2 percent lie outside the 92 percent confidence interval and wage decreases of 3 percent lie outside the 95 percent confidence interval.
Keywords: I12; I13; I18; J22; J28; J32; 330; sick pay mandates; sick leave; medical leave; employer mandates; employment; wages; synthetic control group method (SCGM); Quarterly Census of Employment and Wages (QCEW0; United States (U.S.)